2007
DOI: 10.1152/ajprenal.00427.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for gut factor in K+ homeostasis

Abstract: We tested the hypothesis that K(+) intake is sensed by putative K(+) sensors in the splanchnic areas, and renal K(+) handling is regulated by this signal. K(+) was infused for 2 h into overnight-fasted rats via the jugular vein (systemic infusion), hepatic portal vein (intraportal infusion), or stomach (intragastric infusion) (n = 5 each), and plasma K(+) concentration ([K(+)]) and renal K(+) excretion were measured during the 2-h preinfusion, 2-h K(+) infusion, and 3-h washout periods. During systemic K(+) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 24 publications
5
61
0
Order By: Relevance
“…The tray was replaced every hour to collect urine passed. To obtain a constant flow of urine, animals were infused with a constant volume (4.1 ml/h) of fluid (saline or saline ϩ KCl during K ϩ infusion) throughout the experiment (15). This infusion volume did not appear to affect K ϩ excretion, as the baseline K ϩ excretion rate was indistinguishable from the basal rate of K ϩ excretion measured in fasting rats without fluid infusion between 7 AM and 7 PM (data not shown).…”
Section: Animalsmentioning
confidence: 95%
See 1 more Smart Citation
“…The tray was replaced every hour to collect urine passed. To obtain a constant flow of urine, animals were infused with a constant volume (4.1 ml/h) of fluid (saline or saline ϩ KCl during K ϩ infusion) throughout the experiment (15). This infusion volume did not appear to affect K ϩ excretion, as the baseline K ϩ excretion rate was indistinguishable from the basal rate of K ϩ excretion measured in fasting rats without fluid infusion between 7 AM and 7 PM (data not shown).…”
Section: Animalsmentioning
confidence: 95%
“…Feedforward control of K ϩ homeostasis was supported by our recent study (15) that examine the effects of K ϩ infusion into stomach vs. hepatic portal vein or a systemic vein on plasma [K ϩ ] and renal K ϩ excretion in rats. Our results indicated that the K ϩ infusions via these different routes resulted in similar profiles of plasma [K ϩ ] and renal K ϩ excretion in fasting states.…”
mentioning
confidence: 94%
“…14 argued that the increase in serum potassium after a high-potassium meal is too small (0.5 mEq/L) to initiate either of these adaptive responses and that an intestinal signal is responsible for the increase in renal potassium excretion after a high potassium meal. Recent, interesting work from Lee et al 13 further strengthened this observation. Lee et al showed that the administration of potassium by intravenous, intraportal, or intragastric method has a similar effect on plasma potassium and renal potassium excretion profiles in the fasting state but that the administration of a low-potassium meal along with intragastric potassium infusion substantially reduces the increase in plasma potassium and greatly enhances renal potassium excretion.…”
Section: Enteric Modulation Of Renal Sodium and Potassiummentioning
confidence: 79%
“…Elevated serum potassium directly alters potassium excretion by collecting duct cells and thereby promotes kaliuresis. [11][12][13] An elevation in serum potassium concentration also increases aldosterone synthesis, which, in turn, increases kaliuresis. 14 argued that the increase in serum potassium after a high-potassium meal is too small (0.5 mEq/L) to initiate either of these adaptive responses and that an intestinal signal is responsible for the increase in renal potassium excretion after a high potassium meal.…”
Section: Enteric Modulation Of Renal Sodium and Potassiummentioning
confidence: 99%
See 1 more Smart Citation